ASOSIASI ANTARA TUTUPAN KOMUNITAS KARANG DENGAN KOMUNITAS IKAN TERUMBU KARANG DI PESISIR TIMUR PULAU BIAK, KABUPATEN BIAK NUMFOR - Olivia Lana Y Rumkorem; Rahmat Kurnia; Fredinan Yulianda (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2019)
Coral reef ecosystems have many benefits including protect the coast from strong waves and currents and are important in maintaining the ecological system in these waters as habitat, spawning grounds, shelter and food sources for marine biota such as ascidians, sponge, echinoderms, mollusks, and fish. The diversity of reef fishes on the east coast of Biak Island is one of the important resources used as a source of income or food source by residents who earn a living as fishermen. This study aims to analyze the relationship between coral communities and coral reef fish communities on the east coast of Biak Island, Biak Numfor Regency. Observations were done by diving using SCUBA equipment. Observation of the condition of the coral reefs used the PIT (Point Intercept Transect) method and coral reef fish worked by the UVC (Underwater Visual Census) method. Data analysis was running by the Spearman test analysis. The results showed that changes in coral community cover affect reef fish communities. This study concludes that there is an association between coral communities and coral reef fish communities that have a positive linear relationship.